Leisure and cultural identity: an empirical study based on root-seeking summer camp for ethnic Chinese new generation - Wang, Zhenhan; Ye, Sheling; Bei, Li (Frontiers in Psychology, 2024)
Amidst the vast sea of globalization, the preservation of cultural identity is a multifaceted challenge, not only for Chinese youth living abroad but also for every individual in an increasingly interconnected world. Against this backdrop, this study examines the role of rootseeking summer camp in enhancing Chinese cultural identity among the new ethnic Chinese generation(ECNG). Thirty campers participated in the semi-structured interviews. The results indicate that the ECNG lacks clear ethnic consciousness, experiences conflict in community relationships, and lacks opportunities for traditional cultural experiences. As a recreational activity, summer camp exerts an intrinsic influence on campers by facilitating the internalization of leisure motivation, fostering a deepened leisure experience, and promoting strengthened leisure interactions. In addition, it provides campers with external opportunities for leisure education and cultural immersion. Through the synergistic interplay between intrinsic influences and external opportunities, summer camp enhances the cultural identification of the ECNG. The study also noted that the degree of course fun and the behavior of teaching staff may generate pessimistic perceptions of the summer camp. The theoretical contribution of this study is that it explores the relationship between leisure and identity, explains how summer camp activities enhance ECNG's cultural identity, and provides possible references for governments and agencies.